Antiretroviral therapy uptake and predictors of virological failure in patients with HIV receiving first-line and second-line regimens in Johannesburg, South Africa: a retrospective cohort data analysis. Issue 4 (15th April 2022) - Gumede, Siphamandla Bonga; Venter, Francois; de Wit, John; Wensing, Annemarie; Lalla-Edward, Samanta Tresha
Abstract : Objective: This study described the demographics, treatment information and identified characteristics associated with virological failure and being lost to follow-up (LTFU) for patients with HIV on first-line and second-line antiretroviral therapy (ART) regimens in a large South African cohort. Design: A quantitative retrospective cohort study using secondary data analysis. Setting: Seven Johannesburg inner city facilities. Participants: Unique records of 123 002 people with HIV receiving ART at any point in the period 1 April 2004 to 29 February 2020 were included. Measures: Demographic characteristics, ART status, CD4 count information and retention status were collected and analysed as covariates of outcomes (viral load (VL) and LTFU). Results: Of the total study patients, 95% (n=1 17 260) were on a first-line regimen and 5% (n=5742) were on a second-line regimen. Almost two-thirds were female (64%, n=79 226). Most patients (60%, n=72 430) were initiated on an efavirenz-based, tenofovir disoproxil fumarate-based and emtricitabine-based regimen (fixed-dose combination). 91% (n=76 737) achieved viral suppression at least once since initiating on ART and 60% (n=57 981) remained in care as at the end of February 2020. Patients from the community health centre and primary healthcare clinics were not only more likely to be virally suppressed but also more likely to be LTFU. Patients on second-line regimens were less likely to reach viral suppression (adjusted OR (aOR)=0.26, CI=0.23 to 0.28) and more likely to be LTFU (aOR=1.21, CI=1.09 to 1.35). Being older (≥25 years) and having a recent CD4 cell count≥100 cells/µL were predictors of viral suppression and retention in patients on ART. Conclusion: Patients on first-line regimens had higher VL suppression rates and were more likely to remain in care than those on a second-line regimen. Being younger and having low CD4 cell counts were associated with poor outcomes, suggesting priority groups for ART adherence support.